Observations on myxozoans (Myzozoa: Myxosporea) and the spatial and temporal variation in parasite assemblages of the nosestripe klipfish, Muraenoclinus dorsalis Bleeke, 1860 (Perciformes: Clinidae) - Tang, Laura (Department of Biological Sciences, 2014)
The coast of South Africa is one of the most biologically diverse marine systems in the world but little is known about the parasites occurring in this environment. A survey of the parasites of an intertidal clinid, Muraenoclinus dorsalis Bleeker, 1860, captured from Granger Bay, Kommetjie and Jacobsbaai, South Africa during Summer 2008/2009 and Winter 2009 revealed twenty-three parasitic species. Five myxozoans, all likely new to science, were found to infect M dorsalis. Ceratomyxa sp. and Sphaeromyxa sp. 1 were found in the gall bladder and bile ducts, Kudoa sp. in skeletal muscle, and a Myxobolus sp. on the eyes. Spores of Ortholinea sp. were also detected in gall bladder squashes, but the actual location of infection is unknown. The endoparasite community composition and structure, and their persistence over space and time were also probed. Non-metric multidimensional scaling, cluster analysis and Analysis of Similarity showed that community composition during both summer and winter differed most between Kommetjie and Jacobsbaai, the sites geographically furthest apart. This observation implies a decay in similarity over geographic distance. The endoparasite component communities from Granger Bay showed no significant dissimilarity in composition between summer and winter while the component communities from Kommetjie showed little dissimilarity (Global R: 0.105; p-value = 0.002). These results suggest that season or seasonassociated factors play weak roles at both localities. Contrastingly, the summer and winter component communities from Jacobsbaai showed significant dissimilarity (Global R: 0.201; pvalue = 0.003) because of the higher parasite load in winter. This is attributed to the sheltered nature of Jacobsbaai, where violent winter waves do not disturb the fish but rather push up the tide thereby extending the submergence period of M dorsalis. A longer period of submergence may provide parasites with increased opportunities to infect a host. Nestedness analysesconfirmed a nested subset structure in all component communities, likely a result of differentiated colonization, passive sampling, or a combination of both. This result lends evidence to the theory that parasite community structure is persistent over space and time and that there are laws in parasite ecology.